Avaliação da resposta imunológica de uma formulação vacinal contra leishmaniose visceral constituída de peptídeos sintéticos da gp63 de leishmania major com predição para MHC-I/MHC-II - Paciello, Maurício Oviedo (Universidade Federal do Tocantins, 2017)
Leishmaniasis is considered one of the six endemics priority in the world. Its severity will depend on the contaminating species, and may range from a relatively mild cutaneous lesion to a visceral infection that can be fatal in the absence of treatment. Now a days, one of the major challenges encountered in studies of the increasing urbanization of visceral leishmaniasis (VL) is the development of highly effective vaccines to induce protection against Leishmania infection. In this context, the present study aimed to evaluate the humoral and cellular immune response of a new vaccine formulation against visceral leishmaniasis (VL) using hamster (Mesocricetus auratus) as an experimental model. The vaccine formulation consists of two synthetic peptides of the gp63 protease in Leishmania major with high prediction of MHC-I and II. The preparation of the peptides started with their prediction, using SYFPEITHI software, followed by their chemical synthesis, using the solid phase methodology, according to the standard protocol of Merrifield (1963). The peptides’ purification and identification of th was performed by liquid chromatography under low pressure conditions. Nine animals aged 4-8 weeks were randomly selected and divided into three experimental groups: the control group, the group immunized with the adjuvant montanide (ISA) and the group immunized with peptide + adjuvant montanide association (Pep + ISA), each group containing three animals. Inoculations of the different experimental groups were administered subcutaneously at three vaccine doses at 14 day intervals. The control group received 100 μL of 0.85% sterile saline, the ISA group received 30 μL of the Montanide ISA-61VG oily adjuvant diluted in 70 μL of 0.85% saline and the Pep + ISA group received 30 μL of the MHC-I peptide + 30 μL of the MHC-II peptide, emulsified in 30 μL of the Montanide ISA-61VG adjuvant and diluted in 10 μL of 0.85% saline solution. Six days after the last vaccine dose, the animals were sedated with Chlortamine® (50 mg / mL) intraperitoneally and the blood collected to proceed with hematological, biochemical and serological analyzes. After 205 days of the last vaccine dose, the animals were euthanized and their spleens collected for evaluation of the lymphoproliferative response. The biochemical results showed that the vaccine composition had no toxic action, presenting serum levels of urea, creatinine and hepatocellular enzymes within the normal range for renal and hepatic functioning. The vaccine formulation also showed significant levels of antibodies and the existence of immunological memory evidenced by the increase in lymphoproliferative activity in splenocyte cultures, when compared to the group that received the vaccine with the other experimental groups.